I think I have this, but want to make sure...
Let g(x)= x^2 f(x)
What does g'(x)=?
Using the power rule I come up with (2x * f(x) * f'(x) )*(x^2 * f'(x))
Is that right?
Any help would be greatly appreciated.
I think I have this, but want to make sure...
Let g(x)= x^2 f(x)
What does g'(x)=?
Using the power rule I come up with (2x * f(x) * f'(x) )*(x^2 * f'(x))
Is that right?
Any help would be greatly appreciated.
Nope, you have to use the product rule :
$\displaystyle [uv]'=u'v+uv'$, where $\displaystyle u=x^2$ and $\displaystyle v=f$